Chiral differentiation of the noscapine and hydrastine stereoisomers by electrospray ionization tandem mass spectrometry. (January 2015) - Nagy, Tibor; Kuki, Ákos; Antal, Borbála; Nagy, Lajos; Purgel, Mihály; Sipos, Attila; Nagy, Miklós; Zsuga, Miklós; Kéki, Sándor
<x xml:space="preserve">Abstract</x> Energy‐dependent collision‐induced dissociation (CID) of the dimers [2 M + Cat]+ of the noscapine and hydrastine stereoisomers was studied where Cat stands for Li+, Na+, K+ and Cs+ ions. These dimers were generated 'in situ' from the electrosprayed solution. The survival yield (SY) method was used for distinguishing the noscapine and hydrastine dimers. Significant differences were found between the characteristic collision energies (CE50, i.e. the collision energy necessary to obtain 50% fragmentation) of the homo‐ (R, R; S, S) and heterochiral (R, S; S, R) stereoisomers. To distinguish the enantiomer pairs L‐, D‐tyrosine ([M + Tyr + Cat]+) and L‐, D‐lysine ([M + Lys + Cat]+) were used as chiral selectors. Furthermore, these heterodimers [M + amino acid + Cat]+ were also applied to determine the stereoisomeric composition. It was found that the characteristic collision energy (CE50) of the noscapine and hydrastine homodimers ([2 M + Cat]+) was inversely proportional to the ionic radius of the cations. Furthermore, the structures of the dimers [2 M + Cat]+ were studied by high level quantum chemical calculations. Copyright © 2015 John Wiley & Sons, Ltd.